Father involvement in the first year of life: Associations with maternal mental health and child development outcomes in rural Pakistan. (September 2019) - Maselko, Joanna; Hagaman, Ashley K.; Bates, Lisa M.; Bhalotra, Sonia; Biroli, Pietro; Gallis, John A.; O'Donnell, Karen; Sikander, Siham; Turner, Elizabeth L.; Rahman, Atif
Abstract: The contribution of fathers to child development and maternal mental health is increasingly acknowledged, although research on this topic outside of high income countries is limited. Using longitudinal data, we characterized father involvement in a rural setting in Pakistan and investigated the link between father involvement in the first year of life and child development and maternal depression. Data come from the Bachpan study, a birth cohort established in the context of a perinatal depression intervention. Father involvement was mother reported at 3 and 12 months postpartum and covered domains such as playing with or soothing the infant. Child outcomes included growth at 3, 6 and 12 months postpartum, socioemotional development at 6 months (Ages and Stages Questionnaire-socioemotional), and developmental milestones at 12 months (Bayley Scales of Infant and Toddler Development, BSID)). Maternal depression was assessed at 3, 6, and 12 months postpartum. Roughly 20% of the fathers were temporarily non-resident. Among the rest, most mothers reported that fathers were involved: for example, approximately 40% reported that the father plays with the baby on a typical day. We observed no clear pattern of association between 3-month father involvement and child growth at any time point; however, 12-month father involvement was cross-sectionally inversely associated with child growth. We observed a protective pattern of association between 3-month father involvement and 6-month child socioemotional development. For the BSID domains, while almost all effect estimates suggested a protective association with higher levels of father involvement/father being temporarily non-resident, the magnitude of the estimates was smaller and most 95% confidence intervals crossed the null. Finally, there was a trend toward greater father involvement/being temporary non-resident predicting lower levels of maternal depression. Using longitudinal data, these results provide new evidence about the association between father involvement, and both child development and maternal mental health. Highlights: Most mothers reported at least modest levels of father involvement. A fifth of fathers were away from home and not directly involved with the infant. Father involvement was either not, or inversely, associated with child growth. Father involvement was associated with better socioemotional indicators; the link with other developmental markers was weaker.